STRENGTHENING THE CAPACITY OF PURPLE SWEET POTATO CHIPS MSMES THROUGH DIGITALIZATION OF FINANCIAL MANAGEMENT AND MARKETING IN THE TECHNOLOGY ERA - Fatimah Fatimah; Rahmawati Rahmawati; Deasy Soraya A Aminartha Putri; Arfianty Arfianty; Nasrullah A; Dwi Ananda; Alvira Alvian (Universitas Muhammadiyah Sidenreng Rappang, 2026)
This community service activity aims to increase the business capacity of the